Model of halal management practices in Islamic banking: empirical evidence from Bank Syariah Indonesia - Adinugraha, Hendri Hermawan; Shulthoni, Muhammad; Al-Kasyaf, Muhammad Zheeva (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2025)
Purpose – This research analyzes the halal management practice model implemented at the Bank Syariah Indonesia (BSI) Pekalongan branch in maintaining compliance with Sharia principles. Method – This research uses a qualitative method with an interpretative approach. Data collection was done through in-depth interviews, observation, and document analysis. The research results were validated by triangulating data sources, methods, and theories. Findings – The results showed that the BSI Pekalongan branch implemented a strict supervisory system to ensure that all transactions and services followed Sharia principles. Transparency in contracts and halal-based fund management are the main factors that build customer trust. Islamic financial education strategies play a role in increasing customer loyalty to bank products and services. Challenges in Islamic financial literacy and technology utilization still hinder the improvement of halal management efficiency. This research provides insight for Islamic banking stakeholders to increase the effectiveness of halal management in building customer trust and loyalty. The BSI Pekalongan branch can improve its competitiveness and ensure full compliance with Sharia principles by strengthening its supervision through transaction transparency and digitalization of halal services. Implications – Theoretically, this research enriches halal management studies by emphasizing Sharia compliance, transparency, and innovation in digital services. Practically, it guides Islamic banks in strengthening governance and customer trust.